Mechanical and hygrothermal analysis of 3D printed carbon fibre reinforced plastics - Das, Shomir (Nanyang Technological University, 2020)
This final year project includes a literature review on additive manufacturing processes, carbon fibre reinforced composites, and curing techniques for composite materials. The experiments conducted for the mechanical properties of the specimens are tensile and 3-point bending tests of the 3D printed composite specimens. The composite used is a carbon fibre reinforced plastic that consists of nylon and carbon fibre, called Onyx. There is limited research done on the Onyx material to date due to it being a relatively new production. This project aims to bridge this gap as well as provide research information for any future paper references. A hygrothermal study is also done in this project in order to evaluate if the specimens; and by extension the Onyx material, are affected by the addition of heat and moisture. Specimens were printed at a different angle to previous reports in order to evaluate if this new printing angle is more suited for the composite. 16 specimens were printed in total for this project, with 12 for bending test and 4 for tensile tests. Properties to be recorded from these tests were the respective strength and elastic moduli of the specimens. Theoretical calculations of these properties were also made for comparison purposes. Any potential errors or limitations, as well as suggestions for improvements, were also discussed in this paper.